Analisis Mutu Layanan Pendidikan di SMA Negeri 1 Indralaya Kabupaten Ogan Ilir - Rini Anggun Sari (UNISAN JURNAL, 2024)
This research aims to analyze the quality of educational services at SMA Negeri 1 Indralaya, Ogan Ilir Regency. The research method used is a descriptive analysis method with a quantitative approach. Data was collected through questionnaires distributed to students, parents and teachers at the high school. Data collection was carried out using a simple random sampling technique. Data analysis was carried out using descriptive statistical techniques, including mean, median, and percentage. The research results show that the quality of educational services at SMA Negeri 1 Indralaya has several weaknesses in several aspects. Aspects of physical facilities, such as classroom and laboratory conditions, show a low level of satisfaction. Apart from that, the lack of supporting facilities, such as adequate libraries and adequate sports facilities, is also a major concern. On the other hand, aspects of the learning process show relatively high levels of satisfaction, although there is still room for improvement in terms of increasing student engagement and using innovative teaching methods. From a management perspective, coordination between teachers, students and parents needs to be improved to increase the effectiveness and efficiency of the education process. This research provides valuable insight for schools and related stakeholders to improve the quality of educational services at SMA Negeri 1 Indralaya, Ogan Ilir Regency, as well as to improve overall educational conditions.